2015
DOI: 10.7860/jcdr/2015/14170.6235
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Immunohistochemical Analysis of Langerhans Cells in Oral Mucosa, Oral Lichen Planus and Oral Squamous Cell Carcinoma

Abstract: A better understanding and clarity of LCs is pivotal for designing novel or improved therapeutic approaches that will allow proper functioning of LC's in patients with OLP and OSCC, thus significantly reducing the morbidity of OLP and OSCC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
2
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 12 publications
0
4
2
1
Order By: Relevance
“…Quantification of positive cells was performed by a single pathologist using a light microscope (Nikon, Tokyo, Japan) with a 40× eyepiece in five sequential fields randomly selected . In the OSCC group, cells were counted in the epithelial nests and surrounding stroma.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantification of positive cells was performed by a single pathologist using a light microscope (Nikon, Tokyo, Japan) with a 40× eyepiece in five sequential fields randomly selected . In the OSCC group, cells were counted in the epithelial nests and surrounding stroma.…”
Section: Methodsmentioning
confidence: 99%
“…The antibody dilutions, clone, AR used, stained cells and positive controls are given in Table 1 Quantification of positive cells was performed by a single pathologist using a light microscope (Nikon, Tokyo, Japan) with a 409 eyepiece in five sequential fields randomly selected. 17 In the OSCC group, cells were counted in the epithelial nests and surrounding stroma. In the OED group, cells were counted in the epithelial layer and in the lamina propria.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Это обстоятельство, по-видимому, можно трактовать как косвенный аргумент в пользу предположения о том, что для полноценного функционирования ДК должны взаимодействовать с высокодифференцированными клетками плоского эпителия. В определенной степени предположение подтверждается данными исследований, в которых показано, что наибольшее количество КЛ обнаруживалось в высокодифференцированных опухолях, наименьшее -в низкодифференцированных новообразованиях [10].…”
Section: Discussionunclassified
“…This study has shown how LCs increase significantly from a mild or moderate to a severe inflammatory state. A study by Maloth et al (2015) compared LCs data in oral Lichen planus (OLP) and oral squamous cell carcinoma (OSCC), by anti-S-100 antibodies. The study aimed to demonstrate the function of LCs in local immune response.…”
Section: S-100mentioning
confidence: 99%
“…Histomorphometric quantification was made only on S-100 positive cells, excluding those of the basal layer, identified as melanocytes. The positivity of the reaction has shown that LCs play crucial roles in various oral pathological conditions ( Maloth et al, 2015 ). Also, in a study on the histiocytosis of LCs in an adult with diabetes insipidus conducted by Allen et al (2019) , the anti-S-100 antibody was used to highlight LCs in the tissue samples studied.…”
Section: S-100mentioning
confidence: 99%